2010
DOI: 10.1088/1748-3182/6/1/014001
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of desiccating insect wings

Abstract: The stiffness of insect wings is typically determined through experimental measurements. Such experiments are performed on wings removed from insects. However, the wings are subject to desiccation which typically leads to an increase in their stiffness. Although this effect of desiccation is well known, a comprehensive study of the rate of change in stiffness of desiccating insect wings would be a significant aid in planning experiments as well as interpreting data from such experiments. This communication pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…For each wing, we performed five consecutive stiffness measurements in the un-manipulated state, and another five measurements immediately following splint application (either the joint splint or control splint treatment). All stiffness measurements were completed within 30 min of wing removal, to minimize the gradual effects of wing stiffening caused by desiccation [33]. We used the median EI value from each set of pre-and postmanipulation measurements to calculate percent increase in chordwise flexural stiffness.…”
mentioning
confidence: 99%
“…For each wing, we performed five consecutive stiffness measurements in the un-manipulated state, and another five measurements immediately following splint application (either the joint splint or control splint treatment). All stiffness measurements were completed within 30 min of wing removal, to minimize the gradual effects of wing stiffening caused by desiccation [33]. We used the median EI value from each set of pre-and postmanipulation measurements to calculate percent increase in chordwise flexural stiffness.…”
mentioning
confidence: 99%
“…Ha et al (2013) found fundamental frequency (lowest mode) exceeded wingbeat frequency for all insect groups tested except Hymenopterans, while we found the lowest mode exceeded wingbeat frequency for A. mellifera (Hymenoptera). Ha et al (2013) measured the first longitudinal mode for the wings of several species of insect, but on excised wings, which are stiffer than in vivo wings (Mengesha et al, 2011). Our preliminary trials of excised wings suggested that once the wings had dried, resonance frequencies of this mode increased by 32% (from 340 Hz to 450 Hz), 75 min after wing removal from the animal (n=1), which is why we conducted our primary experiment on wings attached to the animal.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they measured the resonance of excised wings, rather than in situ. Once removed from the animal, insect wings dry (lose mass) and stiffen (Mengesha et al, 2011), both of which should increase resonance frequency relative to the in vivo condition. Ha et al (2013) measured either isolated forewings or hindwings (depending on species), but in most of the species, the forewing/hindwing pair is mechanically coupled during flight.…”
Section: Introductionmentioning
confidence: 99%
“…1C). To avoid the desiccation that occurs in isolated wings (Mengesha et al, 2011), we affixed live, intact insects to a custom-designed brace attached to a rotational motor and spun them at high frequencies, forcing the tip of the left forewing to repeatedly collide with the surface of a leaf ( Fig. 1D; supplementary material Movies 1-3).…”
Section: Introductionmentioning
confidence: 99%